Scrapie-Responsive Gene 1 Promotes Chondrogenic Differentiation of Umbilical Cord Mesenchymal Stem Cells via Wnt5a - Yuchuan Zhou; Tian Zheng; Lin Li; Yangfang Guo; Jiayu Xiao; Jin Wang; Zhiqin Du; Hui Gao; Weiwei Tang; Liusan Yang; Haiyan Hu; Xiaodan Wang; et al. (Stem Cells International)
Objective. Repair of cartilage defects, a common condition resulting from many factors, is still a great challenge. Based on their chondrogenic differentiation ability, mesenchymal stem cell- (MSC-) based cartilage regeneration is a promising approach for cartilage defect repair. However, MSC differentiation into chondroblasts or related cell lineages is elaborately controlled by stem cell differentiation stage factors and affected by an array of bioactive elements, which may impede the efficient production of target cells. Thus, identifying a single transcription factor to promote chondrogenic differentiation is critical. Herein, we explored the mechanism by which scrapie-responsive gene 1 (SCRG1), a candidate gene for cartilage regeneration promotion, regulates chondrogenic differentiation of MSCs. Methods. Expression of SCRG1 was detected in umbilical cord-derived MSCs (UCMSCs) by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and immunohistochemical analysis during chondrogenic differentiation. The function of SCRG1 in chondrogenic potential was evaluated after gene knockdown or overexpression by lentiviral vectors. Finally, a rabbit cartilage defect model was established to evaluate the effect of SCRG1 on cartilage repair in vivo. Results. Expression of SCRG1 was upregulated during in vitro chondrogenic differentiation of UCMSCs. SCRG1 knockdown inhibited chondrogenic differentiation of UCMSCs, while SCRG1 overexpression promoted chondrogenic differentiation of UCMSCs in vitro. In addition, UCMSC overexpressing SCRG1 promoted cartilage repair in vivo. Mechanistically, SCRG1 promoted chondrogenic differentiation via upregulation of Wnt5a expression and subsequent inhibition of β-catenin. Conclusion. Our results showed that SCRG1 promotes chondrogenic differentiation of UCMSCs by inhibiting canonical Wnt/β-catenin signaling through Wnt5a. Our findings provide a future target for chondrogenic differentiation and cartilage regeneration.